Creep fracture parameter C* solutions for semi‐elliptical surface cracks in plates under tensile and bending loads. Issue 1 (4th October 2021) - Wang, Kai; Wang, Guozhen; Tu, Shantung; Xuan, Fuzhen
Abstract: In order to predict and assess creep life for plate structures with semi‐elliptic surface cracks under high temperature condition, the accurate calculation of the creep fracture mechanics parameter C* is a critical step. In this paper, the effects of crack sizes, plate geometries, and material creep properties on the parameter C* have been investigated under tensile and bending loads by extensive finite element analyses. Based on the results, the creep influence functions Hc for calculating C* values were obtained and fitted into equations for surface cracks in plates under both loads. The equations have been verified by finite element calculations. The C* solutions were obtained through these equations which are suitable for wide ranges of crack sizes, plate geometries, and materials.